New and interesting records of Lepidoptera from the southern Amur Region, Russia (Insecta: Lepidoptera) - E. S. Koshkin (SHILAP)
The paper presents data about new records of 21 rare species of Lepidoptera from nine families in the Russian part of the Southern Amur Region (the Khabarovsk Krai and the Jewish Autonomous Oblast’). One genus and species (Siglophora sanguinolenta (Moore, 1888) was first discovered in Russia. In addition, Pryeria sinica Moore, 1877, Stauropus basalis Moore, 1877, Catocala eminens Staudinger, 1892, and Acrodontis kotshubeji Sheljuzhko, 1944 are provided for the Khabarovsk Krai for the first time. Stauropus basalis was also first found in the Jewish Autonomous Oblast’. The second locality of Xylena formosa (Butler, 1878) in Russia is given. The presence of Rhodinia jankowskii (Oberthür, 1880) on the territory of the Khabarovsk Krai was confirmed. The new localities of seven species are the northernmost in their ranges. A new record of Marumba jankowskii (Oberthür, 1880) from the vicinity of the Malmyzh village is the north-easternmost within the species range.